Development of Client Server-Based Queuing Applications at The Samsat Gowa Office - Arsan Kumala Jaya; Akbar Hendra; Muhammad Sabirin Hadis; Muhammad Rizal; Randy Angriawan; Annisa Nurul Puteri (Ceddi Journal of Information System and Technology (JST), 2022)
The government has established a SAMSAT (One-Stop Manunggal Administration System) office which has duties in the motor vehicle tax service. Queuing activities make people spend their time waiting. Therefore, it is necessary to create a queuing system that can inform the estimated queue time remotely. The queuing system does not require users to wait physically, so the waiting time needed to queue can be used by taxpayers to carry out their own personal and work activities that are more useful. Queuing application development aims to develop queuing service features from previous applications which only provide queued information on taxpayers. Features developed in the form of queuing data processing with different activities, monitoring information on time and queue status periodically. The research method used is SDLC (Software Development Life Cycle) with a prototype model. The test results using the Gray Box Testing method show that queuing applications in government agencies providing motorized vehicle tax services have been successfully developed.